Occult Retraction: Cornelius Agrippa and the Paradox of Magical Language - Miles, Chris (Routledge Journals, Taylor & Francis Ltd, 2008)
Recent work on the relationship between rhetoric and magic has tended to pivot around the issue of magic's perceived identification of signifier and signified and what that might mean for its relationship to larger theological, empirical, and rhetorical approaches to language. This article seeks to problematize the assumptions underlying this issue through an examination of the work of Cornelius Agrippa (1486-1535), the author of what is commonly regarded as the European Renaissance's most influential magical text, De occulta philosophia libri tres (1533). In investigating the rhetorical strategies contained in Agrippa's famously ambiguous retraction of his occult works we may uncover an equally polysemic stance toward the ability of language to deal with both the everyday world and the realm of the sacred, a stance that uses textual instantiations of paradoxes of self-reference to forcefully undermine the apparently paradigmatic magical identification of signifier and signified.